Determinación de la carga laboral para la gestión de talento humano de la empresa Grupo Sur. - Balarezo Cárdenas, Licenia Estefanía (2020)
The present investigation shows a process to be continued to determine the labor load in a training company called Grupo Sur, this is born of the need of supporting the decisions of the hierarchic levels in the company, which allows to obtain the work times based on the activities that the workers make in the working day. The areas in which the investigation was faced were the administrative and the sales areas, in the first investigation several dissent declarations were evidenced between the workpeople and Superiors like the chief of the Human Talent Area, affecting to two parts as physical, psychical, mental, as productive and economic. The workload is not a frequently discussed issue within the organization of the company, so in most of these it is not known what it is, for what it is, how to manage and implement it, it is to be reconsidered, that there are not a large number of studies on the subject. However, the present project shows that it is an administrative tool that can be used by any company that wants to know the activities of an employee, what he does exactly, what times he requires, affectations, conditions and risk factors in the job. In this study a qualitative approach was used, by means of a descriptive methodology and it was used as an instrument of investigation the observation card to compile the information. In accordance with the regulations, the normal working day consists of 8 daily hours or 40 weekly hours, in this case, by means of the development of the investigative process it was evidenced that if there is a workload in the company, where the sales area presents from 11 to 13 working hours and the administrative area presents days from 9 to 11 daily hours, it was also known that there are physical, psychical and mental loads which affect to the working staff when they carry out certain activities and these ones are related to the used times. In conclusion, it was possible to know that the workload exists and that it may affect the working environment but that the necessary corrective measures are taken, with the study and results obtained, the managers will be able to analyze and make decisions which improve the worker's quality of life and the productivity of the company. KEYWORD: WORKLOAD